2021
DOI: 10.1002/qj.4099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relationships between weather patterns and observed lightning activity for Britain and Ireland

Abstract: To understand the climatology of lightning affecting Britain and Ireland and to investigate the large‐scale environments which produce lightning in this region, relationships between mean sea‐level pressure (MSLP) patterns and thunderstorm occurrence are investigated. Using daily data between 2010 and 2019, instances of lightning activity are examined against a set of 30 pre‐defined weather patterns based on MSLP. Metrics relating to thunder area, thunder intensity and duration are introduced and evaluated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 57 publications
2
46
0
Order By: Relevance
“…Peaks on NW-and West-facing coasts of Scotland and Ireland (Holt et al, 2001;Wilkinson and Neal, 2021). Shown in Outer Hebrides and Shetland in Autumn (Perry and Hollis, 2005) General orographic lift Peaks in Cumbria and Manchester basin (Holt et al, 2001).…”
Section: Winter Orographic Uplift Of Unstable Polar Maritime Airmentioning
confidence: 99%
See 1 more Smart Citation
“…Peaks on NW-and West-facing coasts of Scotland and Ireland (Holt et al, 2001;Wilkinson and Neal, 2021). Shown in Outer Hebrides and Shetland in Autumn (Perry and Hollis, 2005) General orographic lift Peaks in Cumbria and Manchester basin (Holt et al, 2001).…”
Section: Winter Orographic Uplift Of Unstable Polar Maritime Airmentioning
confidence: 99%
“…London, Manchester and Dublin-peaks in Spring (Wilkinson and Neal, 2021), hotspot in Manchester in Autumn and Winter (Perry and Hollis, 2005).…”
Section: Urban Heat Islandsmentioning
confidence: 99%
“…Sample size limitations with some of the climatologies, particularly for rarer weather patterns, will add an additional level of uncertainty to the resulting forecasts. This is something that was considered by Wilkinson and Neal (2021) in their UK-based weather pattern application for lightning occurrence. In their study, they derived a gridded seasonal lightning climatology for each weather pattern and then merged these with weather pattern forecast probabilities to produce a gridded forecast probability of lightning occurrence (as in Equation ( 3)).…”
Section: Discussionmentioning
confidence: 99%
“…These include forecasting significant wave heights (Steele et al, 2017, 2018), extreme regional rainfall (Richardson, Neal, et al, 2020), coastal flooding (Neal et al, 2018) and flow from Iceland into UK air space for the rapid assessment of volcanic ash risk on aviation given an active Icelandic volcanic eruption (Harrison et al, 2022). Several research applications have also been investigated, including for meteorological droughts (Richardson et al, 2018; Richardson, Fowler, et al, 2020), bike journeys in London (Brown et al, 2019), temperature‐related excess mortality (Huang et al, 2020) and lightning risk (Wilkinson & Neal, 2021). The examples over Europe demonstrate the value of weather pattern forecasts as a medium‐range forecasting guidance tool, which this study hopes to utilize over India.…”
Section: Introductionmentioning
confidence: 99%
“…Boorman et al (2010) attempted to compare modelling work with observed days of audible thunder over the UK observers, but the study was limited by a variety of factors, including the stations used changing with time, the density of stations being significantly different to the resolution of the climate models, and the surface stations being (naturally) limited to land areas. Wilkinson and Neal (2021) investigated the seasonal occurrence of lightning for different weather scenarios over the United Kingdom using Arrival Time Difference Network (ATDnet) data. Koehler (2020), Reap and Orville (1990), Czernecki et al (2016), and Changnon and co-workers (Changnon et al, 1988;Changnon, 2001) have all published work trying to draw together station data and lightning location network (LLN) data.…”
Section: Introductionmentioning
confidence: 99%